Absolute Chronology for the Beaker Culture Site of Coval Simó (Mallorca, Balearic Islands). Issue 2 (2014) - Coll, Jaume; Ramis, Damià
Abstract : This contribution of the absolute chronology for the Beaker culture presents the results of archaeological research that took place at Coval Simó (Mallorca) between 1998 and 2008. Coval Simó is a rockshelter situated at the summit of one of the mountains that forms part of the northern mountain range of the Serra de Tramuntana. The site provided an exceptional undisturbed context, shielding a small space of only 25 m 2 . Thin sedimentary layers were deposited in a short timespan and later were sealed off by large blocks due to a rockslide falling from the top of the rockshelter. This site has offered significant information related to the occupation of a human group linked to the Bell Beaker culture, and users of other distinctive undecorated pottery vessels. Direct evidence of early island metallurgy was also obtained: smelting slags from local copper minerals. Regarding the methodology used for analysis, short-lived samples were chosen for radiocarbon dating, consisting of bone fragments identified and classified taxonomically. The samples were submitted alternately to two different 14 C laboratories and the obtained results point to a clear horizon for the early human occupation of the site, ranging between about 2300 and 1900 cal BC.